Changing incidence of infantile hypertrophic pyloric stenosis. Issue 8 (August 1983) - Knox, E G; Armstrong, E; Haynes, R
Abstract : The incidence of infantile hypertrophic pyloric stenosis was measured in the West Midlands Health Region between 1974 and 1980. It increased from 2.1/1000 Caucasian births in 1974 to 3.5/1000 in 1980 and reflects a reported increase in Central Scotland. Several artefacts were excluded--for example, repeat admissions to the same hospital, transfers to other hospitals, and changes in treatment and in diagnostic standards. Two main demographic changes were excluded as explanations, ethnic changes and changes in the birth rank distribution. The increase is therefore considered real and may be related to changes in breast feeding practice.